2022
DOI: 10.1038/s41467-022-32820-0
|View full text |Cite
|
Sign up to set email alerts
|

Achieving efficient power generation by designing bioinspired and multi-layered interfacial evaporator

Abstract: Water evaporation is a natural phase change phenomenon occurring any time and everywhere. Enormous efforts have been made to harvest energy from this ubiquitous process by leveraging on the interaction between water and materials with tailored structural, chemical and thermal properties. Here, we develop a multi-layered interfacial evaporation-driven nanogenerator (IENG) that further amplifies the interaction by introducing additional bionic light-trapping structure for efficient light to heat and electric gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 55 publications
0
58
0
Order By: Relevance
“…The structural characteristics of the BWS evaporator were observed by SEM (JSN–7500 F, Japan) with an accelerating voltage of 5 kV. The UV–Vis absorption spectrum of the BWS evaporator was measured using a Shimadzu UV–3600i Plus UV–vis–NIR spectrophotometer (Shimadzu, Japan) in the range of 190–2500 nm with a resolution of 1 nm, and the light absorption efficiency was calculated by the following formula of A = 1– R using the literatures, [ 9,17 ] where R is the reflection efficiency of the BWS evaporator. Infrared photographs were captured by a HT‐18 IR camera (Hti‐Xintai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The structural characteristics of the BWS evaporator were observed by SEM (JSN–7500 F, Japan) with an accelerating voltage of 5 kV. The UV–Vis absorption spectrum of the BWS evaporator was measured using a Shimadzu UV–3600i Plus UV–vis–NIR spectrophotometer (Shimadzu, Japan) in the range of 190–2500 nm with a resolution of 1 nm, and the light absorption efficiency was calculated by the following formula of A = 1– R using the literatures, [ 9,17 ] where R is the reflection efficiency of the BWS evaporator. Infrared photographs were captured by a HT‐18 IR camera (Hti‐Xintai, China).…”
Section: Methodsmentioning
confidence: 99%
“…The IENG demonstrates an output power density of 11.8 μW cm −2 , which is 6.8 times greater than the previously documented average value with a high evaporation rate of 2.78 kg m −2 h −1 . 177 Altogether, research on electricity generation has shown the potentiality of SIWE devices along with freshwater generation, but these contributions are still small for real-life practices because of their high cost and the techniques involved.…”
Section: Distinguishing Siwe Materials For Different Applicationsmentioning
confidence: 99%
“… , Photothermal materials play a dominant role in solar absorption for evaporation. In the past, a higher absorption coefficient within the entire solar spectrum was the primary objective for designing new photothermal materials, such as plasmonic metal nanoparticles (e.g., AuNPs, AlNPs), , carbon materials (e.g., graphene, multi-walled carbon nanotubes), ,, semiconducting materials, , conjugated polymers (e.g., polypyrrole, polyaniline), , and the transition metal carbide/nitride (MXene) etc. The absorption coefficient and range of previously developed photothermal materials have already been very close to the absorptivity ceiling (≥99%, 200–2500 nm).…”
Section: Introductionmentioning
confidence: 99%